Different Characteristics between Patients with Apical and Non-Apical Subtypes of Stress-Induced Cardiomyopathy - Lee, Sun Hwa; Kim, Won Ho; Lee, Sang Rok; Rhee, Kyung Suk; Chae, Jei Keon; Ko, Jae Ki (Journal of Cardiovascular Ultrasound, 2013)
Stress-induced cardiomyopathy (SCM) is characterized by apical ballooning on echocardiography, but some of SCM patients show non-apical involvement and their characteristics are not well defined. We investigated 56 patients that were diagnosed as SCM and divided them into 2 groups: apical ballooning syndrome (ABS, n = 49, 87.5%) and non-apical ballooning syndrome (N-ABS, n = 7, 12.5%) groups. Patients with N-ABS were significantly younger than those of the ABS group (52 ± 11 vs. 73 ± 10 years, p < 0.001). Types of preceding stressors and clinical presentation including chest pain, pulmonary edema, cardiogenic shock and in-hospital mortality were comparable between the two groups. In the N-ABS group, wall motion score index was significantly lower than in the ABS group (1.61 ± 0.35 vs. 1.93 ± 0.31, p = 0.016). On electrocardiogram (ECG), T-wave inversion (57.1% vs. 95.8%, p < 0.001) were less frequent in the N-ABS than in the ABS group. Furthermore, maximum QT and corrected QT (QTc) intervals in the N-ABS patients were significantly shorter than the ABS patients (QT, 419.9 ± 66.1 vs. 487.3 ± 79.6 ms, p = 0.038; QTc, 479.0 ± 61.9 vs. 568.0 ± 50.5 ms, p < 0.001). Patients with the N-ABS showed not only atypical echocardiographic findings, but also atypical clinical and ECG manifestations. Integrated consideration is needed to reach a diagnosis of the non-apical subtype of SCM.